Kontribusi Pengetahuan Semantik dan Gramatika terhadap Penalaran Kalimat Mahasiswa Jurusan Pendidikan Bahasa dan Sastra Indonesia - Ridwan Ibrahim (Universitas Negeri Malang, 2016)
The purpose of this study was to describe contribution of students' semantic and grammatical comprehension to their reasoning of sentences. The sample consisted of 40 students selected randomly from the students of the Indonesian Language Education, Faculty of Language Education and Arts, State University of Malang. Data were gathered by tests and analyzed by multiple regression. It was found out that the semantic and grammatical comprehension significantly contributes to the students' reasoning. Based on the finding, it could be concluded that students' semantic and grammatical knowledge seemed to be a predictor for the students' reasoning